The effect of visual feedback on balance rehabilitation in people with impaired ankle instability: a systematic review and meta-analysis - Chuan qiu shui Wang; Kun Wang; Liang Sun; Shi qi Liu; Jiong Luo (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Ankle instability is a consequence of ankle injuries that can impair balance and affect an individual’s ability to perform activities of daily living. Consequently, visual feedback is frequently employed in rehabilitation to enhance training outcomes. However, inconsistencies exist in the scientific literature regarding the effect size of visual feedback and the optimal method of delivery. Aim The objective of this systematic review and meta-analysis was twofold: firstly, to conduct a comprehensive assessment of the potential impact of visual feedback on balance exercises for individuals with ankle instability; secondly, to quantify the effects of visual feedback on balance in this population. Methods A total of 10 studies were included in this systematic review and meta-analysis. The review was conducted in accordance with the PERSiST (Implementing Prisma in Exercise, Rehabilitation, Sport Medicine, and Sports Science) guidance. The research was conducted using four databases and was required to be written in English. Additionally, the studies had to involve the provision of visual feedback during balanced rehabilitation. Results The provision of visual feedback has been demonstrated to enhance the efficacy of rehabilitation programs designed to improve balance. Improvement in static, dynamic, and perceptual balance during balance training. The provision of visual feedback was found to simultaneously increase the subjects’ subjective motivation to train and their satisfaction and enjoyment of the rehabilitation training. The results demonstrated that visual feedback improved the Foot and Ankle Ability Measure by approximately 17% (MD = 2.42, 95%CI = 0.72 to 4.12, I²[total] = 0%). Additionally, the provision of visual feedback during the training cycle may positively affect the star excursion balance test (SEBT) (MD = 4.83, 95%CI = 3.09 to 6.56, I²[total] = 21%). Moreover, the Biodex system is expected to demonstrate notable improvements in measures of balance (MD = 0.14, 95% CI = 0.01 to 0.28, I²[total] = 24%). Conclusion The provision of visual feedback in the context of balance rehabilitation has been demonstrated to facilitate beneficial adaptations to balance in individuals presenting with ankle instability. The research included in our analysis demonstrates the positive impact of visual feedback, with nearly all results exhibiting superior outcomes relative to those observed in the absence of visual feedback. Visual feedback can be employed as an “additive” or alternative to conventional rehabilitation for individuals with ankle instability.